Pro SQL Server 2008 Mirroring - Davis, Robert; Simmons, Ken (Apress : Imprint: Apress, 2009)
Pro SQL Server 2008 Mirroring is your complete guide to planning, using, deploying, and maintaining database mirroring as a high-availability option. Mirroring protects you by maintaining one or more duplicate copies of your database for use in the event the primary copy is damaged. It is a key component of any production-level, high-availability solution. This book covers the full spectrum of database mirroring, taking you from the planning phase through the implementation to the maintenance phase and beyond. Easy to follow, step-by-step instructions for beginner and intermediate users In-depth, detailed information for advanced and expert users Covers all phases of database mirroring from planning to sustained maintenance.